Waris Kesetaraan Gender: Komparasi Perspektif Wahbah Az-Zuhaily dan Muhammad Syahrur - Alda Kartika Yudha (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
The problem in inheritance is an unusual problem. Islamic inheritance always intersects with many things that must be considered. Therefore, the study that only focus on Islamic inheritance law without paying attention on the other aspects of being united will cause more problems. The basic assumptions used by some groups are sometimes extreme. In the context of inheritance, Zuhaily and Syahrur's views on the equality of men and women are interesting to reveal. The enthusiasm of both of them fight for justice and inheritance equality between men and women. Therefore, this study aims to describe two well-known Muslim thinkers in relation to inheritance law in Islam. This type of research uses a qualitative approach with library data search. The analysis used is content analysis juxtaposed with socio-cultural analysis to present the reasons for differences of opinion between the two figures. This study found that although there are many similarities between Shahrur and Zuhaily, there are many differences between the two. The most visible differences can be seen in the way both interpret equality and justice inheritance between men and women. If Zuhaily uses more texts, Shahrur relates the text more to the demands and development of the times. When viewed from the aspect of Istinbatul Ahkam, Zuhaily's opinion is stronger. But if you look at the practices of people's lives, the interpretation of Shahrur about inheritance equality looks more relevant.